2000
DOI: 10.1128/jb.182.11.3266-3273.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the sbo-alb Locus of Bacillus subtilis : Identification of Genes Required for Subtilosin Production and Immunity

Abstract: The Bacillus subtilis 168 derivative JH642 produces a bacteriocin, subtilosin, which possesses activity against Listeria monocytogenes. Inspection of the amino acid sequence of the presubtilosin polypeptide encoded by the gene sboA and sequence data from analysis of mature subtilosin indicate that the precursor subtilosin peptide undergoes several unique and unusual chemical modifications during its maturation process. The genes of the sbo-alb operon are believed to function in the synthesis and maturation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 55 publications
1
76
0
Order By: Relevance
“…TrnC exhibited sequence similarity to conserved domains of the Fe-S oxidoreductase arylsulfatase regulatory proteins (AslB), and TrnD had sequences similar to the MoaA family of molybdenum cofactor enzymes. Radical SAM enzymes rarely occur in bacteriocin gene clusters, but they are included in those of subtilosin A and propiocin F (26,27). Sequence alignments indicated that AlbA of subtilosin A exhibits only 19% and 17% identity to TrnC and TrnD, respectively, although AlbA exhibits some features of each individual thuricin CD protein.…”
Section: Resultsmentioning
confidence: 99%
“…TrnC exhibited sequence similarity to conserved domains of the Fe-S oxidoreductase arylsulfatase regulatory proteins (AslB), and TrnD had sequences similar to the MoaA family of molybdenum cofactor enzymes. Radical SAM enzymes rarely occur in bacteriocin gene clusters, but they are included in those of subtilosin A and propiocin F (26,27). Sequence alignments indicated that AlbA of subtilosin A exhibits only 19% and 17% identity to TrnC and TrnD, respectively, although AlbA exhibits some features of each individual thuricin CD protein.…”
Section: Resultsmentioning
confidence: 99%
“…PCR sequences were identified using the basic local alignment search tool and GenBank nucleotide data bank from the National Center for Biotechnology Information, Bethesda, MD, USA (http://www.ncbi.nlm.nih.gov). sboX, encoded a bacteriocinlike product, a new gene with an unknown function, in strain 168 [19], which resides in an open reading frame overlapping the coding region of sbo. While the expression of sboX would result in a 22-amino-acid curtailed peptide in W23-like strains compared to the peptide produced by 168-like strains, which makes it unlikely that SboX is produced by W23-like strains.…”
Section: Subtilosin Genementioning
confidence: 99%
“…The spectrum of activity was investigated and proved antagonism against a wide range of bacteria including Gram-positive and Gram-negative bacteria and both aerobes and anaerobes [18]. The production of mature subtilosin is based on the expression of the sbo-alb *Address correspondence to this author at the Department of Microbiology and Molecular Genetics, University of the Punjab, Quaid-e-Azam Campus, Lahore, Pakistan; Tel: +92-42-99238530; Fax +92-42-99230481: E-mail: shahida@mmg.pu.edu.pk, genetic@brain.net.pk gene cluster encompassing the subtilosin structural gene sbo and genes involved in posttranslational modification, processing of presubtilosin and immunity [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…AlbB, AlbC, and AlbD are required for subtilosin A immunity. AlbB was postulated to be an immunity peptide and AlbC to be involved in subtilosin A export (37). The albABCDEF genes are transcribed from the sboA promoter despite a putative factor-independent transcription terminator present between sboA and albA.…”
mentioning
confidence: 99%
“…The sboA gene, encoding the 43-amino-acid precursor of subtilosin A, was identified with the downstream albABCDEF genes, which are required for processing and modification of the precursor as well as immunity to subtilosin A (37,38). AlbA and AlbF are essential for subtilosin A production and are likely involved in modification and processing of the precursor, respectively.…”
mentioning
confidence: 99%